Effect of Paternal Blue Catfish Strain Effects on Hatchery Fry Production and Performance of Channel Catfish × Blue Catfish F1 Hybrid Fry Production and Fingerling Performance Under Commercial Conditions. (1st October 2016) - Chatakondi, Nagaraj G.; Yant, Roger D.; Dunham, Rex A.
Abstract: This study examined the influence of strain of sire on hybrid catfish embryo production and performance of fingerlings under commercial conditions. Four hundred 4-year-old female Gold Kist strain Channel Catfish Ictalurus punctatus were induced to spawn in eight spawning trials. The stripped eggs were fertilized with the sperm of either D&B or Rio Grande Blue Catfish I. furcatus to produce D&B or Rio Grande hybrid catfish embryos. Testes weight (g/kg body weight [BW]) was higher in Rio Grande (1.98 ± 0.28 g/kg BW) than in D&B (1.02 ± 0.12 g/kg BW) Blue Catfish males. Hatching parameters between Rio Grande and D&B hybrids did not differ. Approximately 100, 000 hybrid catfish fry produced from each spawning trial were stocked in an individual 0.4-ha pond to raise fingerlings. Four ponds of D&B and four ponds of Rio Grande hybrids were stocked in eight ponds of identical conditions at the same time. The mean individual BW of D&B hybrid fingerlings (38.5 g) was higher than that of Rio Grande hybrid fingerlings (32.5 g) at 9 months of age. Mean survival (99.3%), production (8, 875 kg/ha), and feed conversion (1.14) of D&B hybrid catfish fingerlings were superior to Rio Grande hybrid catfish fingerling survival (92.1%), production (7, 664 kg/ha), and feed conversion (1.23), the catfish being raised in replicated earthen ponds under farm conditions. While the D&B strain of sire improved the performance of hybrid catfish fingerlings, it had minimal influence on hybrid catfish fry production. Received December 11, 2015; accepted April 27, 2016